Contemporary Nigerian Artists' Response to Postmodernist Trends and Its Implications for Effective Artistic Growth - Duniya, Giles Gambo; Adewumi, Kehinde (African Journal of Inter/Multidisciplinary Studies, 2023)
The arguably retrogressive development of infrastructures, socio-political systems and technology in most African states casts a shadow of doubt on Africa’s claim to modernity and by extension, postmodernity. Within the context of the arts, the argument of this paper is premised on two questions: Why do some Nigerian artists claim to be post-modern? What is the viability of such a claim, in a country that, one is wondering whether it is even a modern society? To proffer answers to these questions, the paper enunciates a historical overview of contemporary African art and artists vis-à-vis the generalized concept of post-modernity, from the subjective view that its conceptualization and understanding, have a direct influence on contemporary artistic practice and expression. The paper then interrogates certain arts, within the context of their postmodern trend. The paper's conceptual framework is premised on Peroziosi’s (2009) postulation that artworks are reflective of their original time, place, and production circumstances. The authors conclude that contemporary artists’ responses to and their manifestation of postmodernist trends are such that can be categorised into three: Those who aspire faithfully to postmodernist principles; those who are inspired by postmodernism but want to progress their society by socio-political and economic reflections, criticism and advocacies as well as those who ordinarily would not have been artists perhaps, if not for the freedom provided by postmodernism.